2012
DOI: 10.1017/s0021859612000858
|View full text |Cite
|
Sign up to set email alerts
|

Grazing behaviour, herbage intake and animal performance of beef cattle heifers on marandu palisade grass subjected to intensities of continuous stocking management

Abstract: SUMMARYThe ability to adapt to a range of edaphic conditions favours the widespread use of marandu palisade grass in high as well as low input systems of animal production in Brazil. However, little information exists regarding the influence of grazing management practices on sward structure and the carry-over effects on animal responses. The present experiment was planned to evaluate animal behaviour, herbage intake (HI) and nutritive value, herbage accumulation and body weight gain (BWG) of beef cattle heife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 36 publications
6
84
0
31
Order By: Relevance
“…Variations in the grazing process, pasture accessibility, and ease of the leaf harvest resulting from changes in canopy structure may therefore significantly influence forage consumption and, consequently, animal performance. Trindade et al (2007) and Da Silva et al (2013) showed the importance of pasture structure for the control of forage consumption by animals on marandu grass (B. brizantha) pastures. Therefore, the more favorable canopy structure for grazing (Table 2), together with higher CP and IVOMD (Table 2), may explain the higher live weight gain observed for pastures of paiaguás grass during the dry season (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the grazing process, pasture accessibility, and ease of the leaf harvest resulting from changes in canopy structure may therefore significantly influence forage consumption and, consequently, animal performance. Trindade et al (2007) and Da Silva et al (2013) showed the importance of pasture structure for the control of forage consumption by animals on marandu grass (B. brizantha) pastures. Therefore, the more favorable canopy structure for grazing (Table 2), together with higher CP and IVOMD (Table 2), may explain the higher live weight gain observed for pastures of paiaguás grass during the dry season (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, under severe grazing, swards are capable of compensating the smaller LAI through higher rates of tiller appearance and larger population of younger tillers [122], with greater growth potential than older tillers [121]. Since under continuous stocking management a relatively constant proportion of the sward leaf area is removed [139], the remaining leaf area may be sufficient for supplying assimilates, a condition in which the quality of the sward leaf area is crucial for maintaining plant growth [136]. This highlights the importance of the turnover in tiller population and the tillering process in tropical forage grasses, since the ability to replace tillers ensures rapid restoration of photosynthetic tissues and plant growth.…”
Section: Population Dynamics and Stabilitymentioning
confidence: 99%
“…O maior tamanho do bocado é acompanhado de maior tempo requerido para o seu processamento, entretanto os acréscimos na massa de bocado compensam a redução na taxa de bocados, de forma que a velocidade e a quantidade de forragem ingerida pelo animal aumentem (siLva, et al, 2013).…”
Section: Recomendações De Manejo Do Pastejo Com Base Em Respostas Morunclassified